O projektowaniu i sztuce - Błoński, Tadeusz Zdzisław (Instytut Sztuk Pięknych Uniwersytetu Rzeszowskiego, 2019)
Based on personal experience in designing and teaching, the author presents his long-standing fascination with product design and functional structures, describing successive areas of activity, i. e. creating form and function in visual art. The author depicts semantic characteristics of the elements of human environment. Of special interest to him is analyzing the functions of particular elements of man’s living space. The article discusses the issues of contemporary art as a specific phenomenon affected by very fast changes brought about by new technologies (digitalization and new media). New possibilities emerge in art along with digital solutions, present in all spheres of human creative activity, like music, literature and visual arts, including forms connected with movement and light.
On design and art
Keywords: projektowanie; produkt; funkcjonalność; środowisko; sztuka; design; product; functionality; environment; art